2017
DOI: 10.1016/j.healthplace.2017.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of the magnitude of socioeconomic inequalities in mortality: A study of 17 European countries

Abstract: The magnitude of socioeconomic inequalities in mortality differs importantly between countries, but these variations have not been satisfactorily explained. We explored the role of behavioral and structural determinants of these variations, by using a dataset covering 17 European countries in the period 1970-2010, and by conducting multilevel multivariate regression analyses. Our results suggest that between-country variations in inequalities in current mortality can partly be understood from variations in ine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
77
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(93 citation statements)
references
References 51 publications
8
77
0
1
Order By: Relevance
“…A hospital-based study in Ethiopia similarly reported that almost half of the study participants were below average score in all domains of HRQOL [27]. This may mainly be considered as a consequence of the poorly developed economy and low SES, as some evidence has indicated low SES adversely impacts HRQOL [8][9][10][11][12][13][14]41]. Our results also recognized that the reliability of SF-8 items had excellent internal consistency in terms of both Cronbach's α coefficients and item-total correlation.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…A hospital-based study in Ethiopia similarly reported that almost half of the study participants were below average score in all domains of HRQOL [27]. This may mainly be considered as a consequence of the poorly developed economy and low SES, as some evidence has indicated low SES adversely impacts HRQOL [8][9][10][11][12][13][14]41]. Our results also recognized that the reliability of SF-8 items had excellent internal consistency in terms of both Cronbach's α coefficients and item-total correlation.…”
Section: Discussionsupporting
confidence: 62%
“…The latent power of socioeconomic status (SES) in terms of health disparities is evident in the fact that socioeconomic differences in health outcomes have been widely recognized in determining most health circumstances in many countries [7]. Poorer individuals from low-income households are more likely to suffer from diseases, loss of function, cognitive and physical impairment, and exposure to higher morbidity and mortality rates than those from higher-income households [7,8]. However, a previous study concluded that income distribution measures have a small influence, and adjustment with similar parameters made no significant difference to the association between income and health [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A significantly larger proportion of both older age groups (i.e. 35-49 and 50-64 year olds) reported any and multiple (69.5, 67.9% versus 57.3%) HRFs than the youngest age group (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) year olds, Table 3). While having no HRF was the most common profile in the youngest age group (12.8%), seven of the 15 risky HRF profiles, each involving smoking and/ or alcohol, were significantly more common in either the youngest (smoking, alcohol, smoking plus alcohol, smoking plus…”
Section: Hrf Profiles Gender and Agementioning
confidence: 99%
“…More risky HRF clusters were also found in people with lower levels of education [19]. Social inequalities in life expectancy and health between persons at the bottom and those at the top of the social scale are a major concern in public health, and the accumulation of HRFs such as alcohol and smoking has been suggested to explain these differences [13,[20][21][22]. Recent findings suggest that SES may be even more relevant than gender in the accumulation of the four HRFs [23].…”
Section: Introductionmentioning
confidence: 99%